Instability, stationary utilization and effective demand: A synthesis of Harrodian and Kaleckian growth theory - Christian Schoder (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2012)
Within a Kaleckian framework, Harrodian instability and a constant long-run utilization rate are reconciled with the principle of effective demand by endogenizing the capacity output-capital ratio. Its change over time is argued to be a positive function of the utilization rate. As stabilizing forces, distribution and debt dynamics are considered. We argue that, with plausible non-linearities in the investment function, limit cycles consistent with empirical observations for the US can be generated by our model with reasonable parameter values and functional forms. With an endogenous capacity-capital ratio, the paradox of thrift as well as the paradox of cost may hold despite a constant long-run utilization rate.
urn:nbn:de:101:1-2013031310816
Keywords: E12; E16; E22; E32; 330; Kaleckian growth model; Harrodian instability; stationary utilization rate; effective demand; endogenous capital productivity; endogenous cycles